NRCT Clinical Study in to Identify Acetaminophen-Induced Liver Injury Mechanism - Yawo Akrodou (Issues and Development in Health Research Vol. 3, 2021)
Acetaminophen (APAP) (N-acetyl-p-aminophenol) is a chemical molecule used to relieve pain and lower fever in paracetamol medications. The Food and Drug Administration (FDA) advisory group warned in June 2009 about the risk of APAP overdose due to its side effects, which include drug-induced liver disease. In addition, the FDA has begun multicenter non-interventional case-control studies to collect data on APAP toxicity biomarkers in children and adolescents. The National Center for Toxicological Research (NCTR), which is part of the FDA, coordinates the execution of APAP clinical trials in collaboration with other health institutes (hospitals, universities, and clinical centres) around the United States. The goal of these clinical trials is to gather enough data to create a list of biomarkers connected to acetaminophen toxicity that can be matched with specific adduct proteins; this information can then be used to examine and predict future hazards in children who are taking acetaminophen.